Work engagement of high-risk occupation employees: The role of self-efficacy and perceived organizational support - Aulia, Aulia; Rahmawati, Atika; Sari, Selvi Novia (Humanitas: Indonesian Psychological Journal, 2022)
Engagement is vital for every employee at work, especially in occupations with high demands and risks, such as National Agency for Disaster Countermeasure employees. This study aimed to test the contribution of self-efficacy and perceived organizational support on work engagement among employees of the National Agency for Disaster Countermeasure. A quantitative correlational approach was applied in this study, with the population being National Agency for Disaster Countermeasure in  The Special Region of Yogyakarta and Central Java employees in a minimum of a one-year working period. Eighty-eight National Search and Rescue Agency employees participated in this study after selecting through a purposive sampling technique. The data was collected using the modified Utrecht Work Engagement Scale (UWES), self-efficacy scale, and perceived organizational support scale and was then analyzed with multiple linear regression. The results show self-efficacy and perceived organizational support contribute simultaneously to work engagement. Self-efficacy positively contributes to work engagement; likewise, perceived organizational support positively contributes to work engagement. Therefore, this study concludes that self-efficacy and perceived organizational support contribute to work engagement. Moreover, perceived organizational support contributes more to work engagement than self-efficacy. To enhance work engagement among employees of high-risk occupations, perceived organizational support is needed more than self-efficacy.